Stereotyping by omission and commission: Creating distinctive gendered spectacles in the televised coverage of the 2015 Australian Open men's and women's tennis singles semi-finals and finals. (February 2019) - Quayle, Michael; Wurm, Alanna; Barnes, Harley; Barr, Thomas; Beal, Erin; Fallon, Mairead; Flynn, Rachel; McGrath, Dearan; McKenna, Roseanne; Mernagh, Dylan; Pilch, Monika; Ryan, Emma; et al.
This paper explores the way in which announcers created spectacle in the Eurosport coverage of the men's and women's tennis singles semi-finals and finals at the Australian Open 2015. This was an event where gender representations were under global social media scrutiny after two female players were asked to 'twirl' for the audience. We used a two-phase thematic analysis. Semantic thematic analysis showed that more personal descriptions were directed at women than men and these often described off-court features. Descriptions of men included detailed and specific portrayals of physical characteristics, while women's bodies were seldom referred to specifically. Discourse analysis showed that men's games were spoken of as physical clashes between titans. In contrast, women's matches were described in aesthetic rather than physical terms and 'diva-like' personalities and relationships were important features of women's game narratives. While male bodies were described in specific detail where relevant to technical features of the game, women's bodies were only described indirectly and non-specifically. For the women's game, this dialogical repression of specific body talk in combination with a strong focus on aesthetic judgements invoked stereotypes by omission, simultaneously reinscribing gender stereotypes and emphasizing their importance by communicating taboo. These gendered commentaries created distinctive gendered spectacles for the men's and women's events.